The narratives of geographical indications*. Issue 2 (1st May 2014) - Ferrari, Matteo
Abstract The protection of Geographical Indications (GIs) is often conceived as a way to preserve cultural creativity embedded in a specific place. But can GIs be understood as a mode of cultural creativity in their own right? This paper tries to answer this question through a case-study which compares three specific GIs for wines in three different countries (Australia, Italy and Canada). By using an interpretative analysis based on narratives, the paper highlights how GIs are the protagonist of legal narratives in terms of cultural creativity and, at one and the same time, something extrinsic and intrinsic to a given social and productive environment, contributing to defining that same notion of place.